2021
DOI: 10.1016/j.esmoop.2021.100122
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of immune checkpoint inhibitors in metastatic renal cell carcinoma across different treatment lines

Abstract: Background: Immune checkpoint inhibitors (ICIs) have led to a paradigm change in the management of metastatic renal cell carcinoma (mRCC). Prospective trials have focused on ICI treatment in the first or second line. The aim of this analysis is to evaluate the benefit of ICI across different treatment lines. Patients and methods: This is a single-center retrospective study that included mRCC patients who received ICIs in various treatment lines. Objective response rates (ORR), progression-free survival (PFS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
2
6
0
1
Order By: Relevance
“…This is partially due to the exclusion of heavily pre‐treated patients from most clinical trials, which are predominantly arranged in the 1 and 2 L settings. The 4 L setting has not been extensively investigated and these data are mostly from retrospective studies, which do not include patients who progressed to both nivolumab and cabozantinib 4,5,16,17,22–25 …”
Section: Discussionmentioning
confidence: 99%
“…This is partially due to the exclusion of heavily pre‐treated patients from most clinical trials, which are predominantly arranged in the 1 and 2 L settings. The 4 L setting has not been extensively investigated and these data are mostly from retrospective studies, which do not include patients who progressed to both nivolumab and cabozantinib 4,5,16,17,22–25 …”
Section: Discussionmentioning
confidence: 99%
“…After the successes of IO therapy in patients with disease progression on conventional targeted therapies, the randomized phase 3 pivotal CheckMate 214 trial evaluated combination immune checkpoint blockade in treatment-naïve patients with advanced clear cell RCC, resulting in FDA approval of nivolumab plus ipilimumab in patients with International Metastatic Renal Cell Carcinoma Database Consortium (IMDC) intermediate or poor risk. 9 13 14 Thereafter, approaches incorporating dual immune checkpoint blockade with a PD-1 or programmed death ligand 1 (PD-L1) inhibitor along with cytotoxic T-lymphocyte antigen 4 (CTLA-4) inhibition, or immune checkpoint blockade plus a vascular endothelial growth factor (VEGF)-targeted therapy, has become an accepted standard of care for treatment-naïve aRCC on the basis of unprecedented response rates and improved survival. 1–10 Nivolumab is now widely used in monotherapy or in combination for the treatment of aRCC, and the clinical benefit of IOs and their combination with antiangiogenic agents is evident in both untreated and treated patients with aRCC.…”
Section: Introductionmentioning
confidence: 99%
“… 1 9 15 16 In clinical practice, the potential benefits of ICIs or ICI combinations when given beyond the first-line and second-line setting have not been fully elucidated. 9 13 When patients develop resistance or toxicity to immune checkpoint blockade in the first-line treatment of aRCC, a new challenge has emerged regarding how to optimally treat patients in the second-line and beyond in patients who have received prior IO therapy. 1 2 13 Several studies investigated the addition of ipilimumab to nivolumab in a sequential manner and showed that this approach was not always feasible and of limited benefit, with efficacy appearing to be less than that of concomitant nivolumab plus ipilimumab in untreated patients with intermediate/poor-risk disease (CheckMate 214 trial).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-specificity and drug resistance are the main problems faced by conventional treatments for ccRCC (Gai et al, 2020;Zou et al, 2021). And the role of lncRNA in cancer is receiving increasing attention from researchers (Inthagard et al, 2019;Resch et al, 2021).…”
Section: Discussionmentioning
confidence: 99%